The growth kinetics of multilayer graphene grown on Al2O3 substrate by chemical vapour deposition - Ali, May; Abdul-Rashid, Suraya; Hamidon, Mohd Nizar; Md Yasin, Faizah (Elsevier, 2016)
The growth of multilayer graphene (MLG) by chemical vapor deposition (CVD) on a dielectric Al2O3 of (96%) substrate was studied to produce large area thin films with high carrier mobility. The growth of MLG on the deposition of Co-Ni over Al2O3 surface from ethanol decomposition at 700°C-800°C under ambient pressure, was explored using Raman spectroscopy (RS), Field Emission scanning electron microscopy (FESEM) and Transmission electron microscopy (TEM). Experimentally, it was observed that the implementation of ethanol as carbon precursors plays a crucial role in MLG growth, which offer a favourable kinetics model that determine the activation energy and the rate of deposition. Interestingly, MLG grown on dielectric substrates would enable various electrical and chemical sensor applications.